Comparison of the long‐term outcomes of patients with hepatocellular carcinoma within the Milan criteria treated by ablation, resection, or transplantation - Ning‐Ning Zhang; Jian Zheng; Ying Wu; Jia‐Yu Lv; Shu‐Wen Zhang; Ya‐Min Zhang; Wen‐Tao Jiang; Tian‐Qiang Song; Victoria Kim; Samer Tohme; Tian Liu; Wei Zhang; et al. (Cancer Medicine)
Abstract Background Liver transplantation (LT), resection (LR), and ablation (LA) are three curative‐intent treatment options for patients with early hepatocellular carcinoma (HCC). We aimed to develop a prognostic calculator to compare the long‐term outcomes following each of these therapies. Methods A total of 976 patients with HCC within the Milan criteria who underwent LT, LR, and LA between 2009 and 2019 from four institutions were evaluated. Multistate competing risks prediction models for recurrence‐free survival (RFS), recurrence within the Milan criteria (RWM), and HCC‐specific survival (HSS) were derived to develop a prognostic calculator. Results During a median follow‐up of 51 months, 420 (43%) patients developed recurrence. In the multivariate analysis, larger tumor size, multinodularity, older age, male, higher alpha‐fetoprotein (AFP), higher albumin‐bilirubin (ALBI) grade, and the presence of portal hypertension were significantly associated with higher recurrence and decreased survival rates. The RFS and HSS were both significantly higher among patients treated by LT than by LR or LA and significantly higher between patients treated by LR than by LA (all p < 0.001). For multinodular HCC ≤3 cm, although LT had better RFS and HSS than LR or LA, LA was noninferior to LR. An online prognostic calculator was then developed based on the preoperative clinical factors that were independently associated with outcomes to evaluate RFS, RWM, and HSS at different time intervals for all three treatment options. Conclusions Although LT resulted in the best recurrence and survival outcomes, LR and LA also offered durable long‐term alternatives. This prognostic calculator is a useful tool for clinicians to guide an informed and personalized discussion with patients based on their tumor biology and liver function.